EVALUASI KINERJA PEGAWAI DI BANK JATENG KANTOR CABANG PURWOREJO - Prasetyo, Wahyu Aji; Novitasari, Dwi (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
This study aims to 1) Understand the performance of Bank Jateng Purworejo Branch employees. 2) Understand the causes of employee performance at Bank Jateng Purworejo Branch not optimal. 3) Understand the efforts to improve the performance of Bank Jateng Purworejo Branch employees. The method used in this research is descriptive qualitative method. The results showed that because the performance of employees at Bank Jateng Purworejo Branch is not optimal is a) The high workload that exceeds the ability. b) Lack of authority to make decisions while the responsibility to be assumed is very large. c) Benefits that are inadequate or not in accordance with the work load given. d) Unfair and flexible delegation of work that creates social isolation among employees. e) Discrimination can be seen from the way each employee is assessed which is not based on their respective competencies. f) The occurrence of a moral conflict that overrides positive personal principles due to job demands. Efforts to improve the performance of Bank Jateng Purworejo Branch employees are improving work performance, behavior at work, employee attendance, service to customers. While the strategy used as a basis for assessing the success and failure of implementing activities is in accordance with the goals and objectives that have been set in order to realize the vision and mission of Bank Jateng Purworejo Branch, namely by motivating employees, providing an overview of good work such as service to customers, serving problem customers etc., provide confidence training in front of customers, train polite and quality speech, managers monitor directly the work results of employees every day, managers monitor employee attendance, every employee who gets more targets will get a bonus from the center.